2015
DOI: 10.1007/s12603-014-0511-7
|View full text |Cite
|
Sign up to set email alerts
|

Brain metabolism and Alzheimer's disease: The prospect of a metabolite-based therapy

Abstract: The brain is one of the most energy-demanding organs in the body. It has evolved intricate metabolic networks to fulfill this need and utilizes a variety of substrates to generate ATP, the universal energy currency. Any disruption in the supply of energy results in various abnormalities including Alzheimer's disease (AD), a condition with markedly diminished cognitive ability. Astrocytes are an important participant in maintaining the cerebral ATP budget. However, under oxidative stress induced by numerous fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 64 publications
0
24
0
1
Order By: Relevance
“…Interestingly, in a study examining the effects of metal in the diet, retinal Aβ abundance was found to increase dramatically in an aluminum-fed 5xFAD mouse [154]. The potential involvement of metal in AD has been reported before [37, 172]. In two other studies using the 5xFAD mouse, retinal Aβ 40 and Aβ 42 elevation were reported, with notable detection in the RPE [148, 150].…”
Section: Ad-specific Ocular Pathology In Animal Modelsmentioning
confidence: 85%
“…Interestingly, in a study examining the effects of metal in the diet, retinal Aβ abundance was found to increase dramatically in an aluminum-fed 5xFAD mouse [154]. The potential involvement of metal in AD has been reported before [37, 172]. In two other studies using the 5xFAD mouse, retinal Aβ 40 and Aβ 42 elevation were reported, with notable detection in the RPE [148, 150].…”
Section: Ad-specific Ocular Pathology In Animal Modelsmentioning
confidence: 85%
“…Another emerging natural role of Aβ is in immune defense [664] [665], which partly relates to the inflammatory pathways briefly discussed in this review. In combination with molecules that target the energy crisis and mitochondrial disease of AD [161,[666][667][668][669] and distinct metal regulatory pathways [670], there are many promising directions to future therapies in AD that should replace the amyloid-alone strategies as a main priority in efforts to tackle this dreadful disease.…”
Section: Multifunctional Natural Compounds Against Admentioning
confidence: 99%
“…These abnormal situations have to be neutralized or at least mitigated if a living system is to survive. The very fact of consuming O 2 is rife with hazards as this process is inherently associated with oxidative stress [1][2][3]. The reducing factors such as NADH and FADH 2 resulting from the metabolism of a carbon source is oxidized in order to create a proton gradient and a membrane potential, the underlying power behind the synthesis of ATP, the universal energy currency in all cells.…”
Section: Introductionmentioning
confidence: 99%